Tidal Currents and Their Reshaping Impact on Estuarine Morphology: Arus Pasang Surut dan Dampaknya terhadap Morfologi Estuaria - Dea Apriliani; Supiyati Supiyati; Suwarsono Suwarsono (Universitas Muhammadiyah Sidoarjo, 2023)
The Selagan Jaya River Estuary frequently undergoes shape changes, prompting this study to unravel the influence of currents and tides on its morphological evolution. Field measurements encompassing current and tidal data, supplemented by secondary tidal data from TMD and estuary morphology data from USGS, were employed. Findings reveal a mixed semidiurnal tide with a Formzhal value of 0.491 for the Selagan Jaya Estuary. The lowest ebb elevation stands at 0.0117 m, contrasting with the highest flood elevation of 0.6046 m. Flood current velocities range from 0.193 to 1 m/s, while ebb currents span 0.127 to 0.307 m/s. Validation between field and TMD tidal data attains a 98.44% accuracy. Importantly, currents and tides distinctly shape the Selagan Jaya River Estuary; during flood tides, sediment-laden currents ingress, while ebb tides with slower currents hinder sediment egress, underscoring their profound morphological impact. Highlight: Estuarine Morphological Dynamics: Investigates the dynamic nature of the Selagan Jaya River Estuary's shape changes and its underlying processes. Tidal and Current Influence: Unravels the intricate interplay between currents and tides, revealing their significant role in shaping the estuarine morphology. Formzhal Analysis: Introduces the Formzhal value as a key indicator of the estuary's tidal characteristics and their implications for morphological evolution. Keyword: Estuarine Morphodynamics, Currents, Tidal Dynamics, Morphological Evolution, Sediment Transport